Impact of perceived risk and source credibility on intention to use of consumer generated contents for travel planning - Balouchi, Mina; Abdul Aziz, Yuhanis; Abd Rahman, Azmawani; Raja Yusof, Raja Nerina (Faculty of Economics and Management, Universiti Putra Malaysia, 2018)
In recent years, potential travellers still hesitate to adopt consumer-generated contents (CGC) websites as their main source of information for travel planning purposes. This study investigates the effects of source credibility on risk perceived by social media users to facilitate the use of CGC by potential travellers. Technology acceptance model is used and extended with perceived risk as the antecedent of perceived usefulness and ease of use. Further, two dimensions of source credibility theory namely trustworthiness and expertise are added to the model as determinants of perceived risk. Collected data from 211 Iranian online tourists were analysed using SmartPLS to understand the effect of perceived risk on tourists' behavioural intention to use CGC for future travel planning purposes. The findings of the study showed negative effect of source credibility on risk perceived by potential online tourists. The results has shed more lights on the effects of risk perceived by online tourists on their CGC adoption intention in the context of tourism. It can boost the general understanding of CGC adoption by online tourists for travel planning purposes.